Effect of Cassava Pulp from Ethanol Production in Total Mixed Ration on Feed Intake, Digestibility and Growth Performance of Meat Goat - Pornjantuek, Boonserm; Wachirapakorn, Chalong; Cherdthong, Anusorn; Suphrap, Naphongphot; Wongnen, Chantira (Journal of Mahanakorn Veterinary Medicine, 2018)
The objective of this experiment was to study on effect of cassava pulp from ethanol production (CPE) in total mixed ration (TMR) on feed intake, digestibility and growth performance of meat goat. A total of 16 males crossbred Native ´ Anglo-Nubian meat goats (20.28±0.41 kg of initial BW) were used in a completely randomized design (CRD) with 4 levels of CPE at 0, 10, 20 and 30% of TMR. The TMR was formulated containing 14 percent of crude protein and 2.4 Mcal ME/kg DM with concentrate to roughage ratio of 70:30 and rice straw used as the roughage source. The results showed that total feed intake and feed intake (g/kg BW0.75) was cubic decreased (P<0.01) as CPE was increased in TMR and dry matter intake was 2.49-2.94 %BW (P>0.05). Digestion coefficients of DM, OM and CP were quadratic and cubic decreased (P<0.01) respectively, when increased levels of CPE in TMR and digestion coefficients of EE was quadratic increased (P<0.01). Moreover, ruminal pH and plasma urea-nitrogen linearly increased (P<0.01) with increasing the amount of CPE. Although, total volatile fatty acids (TVFA) were significantly different (P<0.01) among dietary treatments. Furthermore, ammonia-nitrogen and final weight of meat goats were not different by dietary treatments (P>0.05). However, weight grain and average daily gain were 4.15-9.03 kg and 46.10-100.30 g/d (P<0.01), respectively. It could be concluded that CPE inclusion in TMR for meat goat at 10% did not effect on feed intake, digestibility and growth performance.